The Hadamard compositions of Dirichlet series absolutely converging in half-plane - M.M. Sheremeta; O.M. Mulyava (Математичні Студії, 2020)
For Dirichlet series with different finite abscissas of absolute convergence in terms of generalized orders the growth of the Hadamard composition of their derivatives is investigated. A relation between the behavior of the maximal terms of Hadamard composition of derivatives and of the derivative of Hadamard composition is established.